Parametric Design Strategies for the Generation of Creative Designs. (September 2014) - Lee, JuHyun; Gu, Ning; Williams, Anthony P.
As one of the emerging Computer-Aided Design (CAD) technologies for digital design and visualisation in the Architecture, Engineering and Construction (AEC) domain, parametric design potentially offers an innovative way of generating new design solutions. Despite this potential, design strategies associated with algorithmic scripting are not well understood. This paper provides a comprehensive understanding of individual design strategies supporting creative solutions in parametric design, using the combined application of protocol analysis and Consensual Assessment Technique (CAT). The article examines the generative and evolutionary aspects of parametric design that play an important role in the generation of creative designs. An in-depth analysis conceptualises designers' parametric design strategies into problem-forwarding strategy and solution-reflecting strategy. The solution-reflecting strategy focusing on the solution space of designing has potential to produce creative solutions by parametric design. A more in-depth understanding of parametric design strategies supports its effective adaptation to better serve the needs of digital design and visualisation in the AEC industry.